Thermal Imaging Used in Building Thermal Evaluation - Brebu Floarea-Maria; Jianu Maria-Roberta; David Viorica; Bălă Alina-Corina (Romanian Journal of Transport Infrastructure, 2023)
Constructors have always tried to use optimal building construction materials to have an energetically efficient building. It was determined that by insulating a building, the energy efficiency increases, but what about the efficiency of the used materials? Of course, every material comes with specific characteristics, but those characteristics are determined in a controlled environment. In our research we tried to determine that those material characteristics are the same when the material is used in a real environment. In this regard, we approached thermal imaging and data was processed using the flir-image-extractor-cli module in Python and FLIR Thermal Studio. Both image and data processing were grouped in specific scenarios, indoor and outdoor, for each insulation material. So, when comparing the temperature difference, we found that the contrast was influenced by the shooting angle and the reflections from the window. Furthermore, we can conclude that imaging, in terms of quantitative and qualitative temperature assessment for energy evaluation of a building, clearly demonstrates the value of the procedure as an aid to research investigations.